Formation of the Xigaze Metamorphic Sole under Tibetan continental lithosphere reveals generic characteristics of subduction initiation - Carl Guilmette; Douwe J. J. van Hinsbergen; Matthijs A. Smit; Antoine Godet; François Fournier-Roy; Jared P. Butler; Marco Maffione; Shun Li; Kip Hodges (Communications Earth & Environment, 2023)
Abstract Metamorphic soles found under allochthonous oceanic lithosphere, or ophiolites, are interpreted as derived from lower plate oceanic crust material accreted to upper plate mantle during intraoceanic subduction initiation. Their metamorphic evolution is inferred to reflect the thermal structure at the site of subduction nucleation, with granulite-bearing soles linked to initiation at hot spreading centers. Here we present garnet Lu-Hf geochronology for the granulite-bearing sole of the Xigaze ophiolite in South Tibet, whose oceanic crust formed ∼130 Ma through continental forearc extension. Our study shows that sole metamorphism was ongoing by 144 Ma, implying that north-directed subduction began at least 14 million years before oceanic forearc spreading. The upper plate at the time of subduction initiation was thus continental, not oceanic. Our results demonstrate that metamorphic characteristics of soles are independent of the specific tectonic setting at the subduction nucleation site and rather provide generic constraints on the subduction initiation process.